Carbamazepine Alleviates Retinal and Optic Nerve Neural Degeneration in Diabetic Mice via Nerve Growth Factor-Induced PI3K/Akt/mTOR Activation - Elsherbiny, Nehal M.; Abdel-Mottaleb, Yousra; Elkazaz, Amany Y.; Atef, Hoda; Lashine, Rehab M.; Youssef, Amal M.; Ezzat, Wessam; El-Ghaiesh, Sabah H.; Elshaer, Rabie E.; El-Shafey, Mohamed; Zaitone, Sawsan A. (Frontiers in Neuroscience, 2019)
Abstract Aim: Diabetic retinopathy causes loss of vision in adults at working-age. Few therapeutic options are available for treatment of diabetic retinopathy. Carbamazepine (CARB), a widely used antiepileptic drug, was recently accounted for its neuroprotective effect. Nerve growth factor (NGF) activates various cascades among which, PI3K/Akt/mTOR pathway has a vital action in NGF-mediated neuronal differentiation and survival. This study evaluated the effect of CARB in the treatment of diabetic retina and unveiled some of the underlying molecular mechanisms. Main methods: Alloxan diabetes model was induced in 36 albino well-acclimatized mice. After establishment of the diabetic model in 9 weeks, mice were assigned to treatment groups: 1) saline, 2) alloxan-diabetic, 3 & 4) alloxan+CARB (25 or 50 mg per kg p.o) for 4 weeks. After completion of the therapeutic period, mice were sacrificed and eyeballs were enucleated. Retinal levels of NGF and PI3K/Akt were assessed using real-time polymerase chain reaction. Further, phospho-TrKA and total TrKA were measured by Western blot analysis. Key findings: Histopathological examination demonstrated that CARB attenuated vacuolization and restored normal thickness and organization of retinal cell layers. In addition, CARB increased pTrKA/TrKA ratio and ameliorated diabetes-induced reduction of NGF mRNA and immunostaining in retina. Additionally, it augmented the mRNA expression of PI3K, and Akt as well as the protein level of the phosphorylated PI3/Akt/mTOR. Significance: Results highlighted for the first time the neuronal protective effect for CARB in diabetic retina which is mediated, at least partly, by activation of NGF/PI3K/Akt/mTOR pathway.